A Case Study of Forecasting Elections Results: Beyond Prediction based on Business Intelligence - Lorenzo, Antonio (2019)
In the field of data analysis, it is common not to distinguish clearly between prediction and forecast. Although the results of both processes may tend to converge, the mechanisms used in each case tend to be completely different. Prediction has to do with statistical extrapolation and estimation and forecasting can consider expert judgments on the subject. A methodology is proposed to carry out this latter task, with a mechanism that uses both historical and current data with the judgement of an expert. The methodology is applied to the case study of the Spanish general elections of April 2019.